Investigating the co-construction of knowledge in an AR inquiry learning environment - Souropetsis, Markos; Kyza, Eleni A. (My University, 2018)
It is increasingly important to examine the processes and outcomes of collaboration at group level. This design-based study investigates upper elementary school students’ co-construction of knowledge in non-formal leaning contexts, during the collaborative use of an augmented reality learning environment at a cultural heritage site. To achieve this aim, we developed a mobile AR learning environment (“CompARe”) to support a collaborative inquiry learning scenario about a unique 6th century wall mosaic of Virgin Mary (in a church on the UNESCO World Heritage Tentative List), considered to be one of the most significant wall mosaics of the early Christian art. This contribution reports on a work in progress; it describes the development process of the “CompARe” AR learning environment and presents the research design to empirically validate the AR environment during a Spring 2018 pilot study with the participation of about 90 5th grade students. Data will be collected using video recordings of students’ collaborative discourse, field observations of the participants during the implementation, log files from the app, and pre- and post-interviews. Student interactions will be examined using an adaptation of the analysis framework on collaborative learning discourse proposed by Weinberger and Fischer (2006). The findings of this pilot study will be reported at the conference; these analyses will support the re-design of the study to examine students’ co-construction of knowledge during the AR inquiry activity, before the larger scale research takes place.
Keywords: Collaboration; Group level; School students’ co-construction; Knowledge; Non-formal leaning context